Pandangan Tokoh Muhammadiyah Di Kota Kupang Terhadap Childfree - Rahma Pramudya Nawang Sari; Yahya Nikmat Nobisa; Jakaria M. Sali; Iskandar Iskandar; Bashita Kartika Paradila; Ahmad Syafii Rahman (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2022)
In marriage that has been prescribed in Islam, having children is one of the goals of marriage because children are the best investment for both parents, religion, society, and the country. But over time, having children is no longer the goal in marriage, there are some couples who choose not to have children. This term is called childfree. In this study, the problems raised by the researcher are: 1) How does the decision of childfree become a life choice for the people of Kupang City. 2) How is childfree according to the view of Muhammadiyah leaders. The purpose of this study was to find out the in-depth reasons for the decision of childfree being the life choice of the people of Kupang City and to find out the views of Muhammadiyah leaders in Kupang City on childfree. The type of research used in this research is field research. The data collection method used in this study was obtained through interviews and documentation. Child-free decisions are decisions that a person makes consciously. Choosing not to have children is not easy, and requires a time-consuming decision-making process that takes into account many factors, including rejection from family members and those closest to you, as well as social pressure. Even so, people with this choice feel that the choice not to have children makes them feel like they are living the free life of their dreams. However, Muhammadiyah leaders in Kupang City did not justify this decision, because it was not in accordance with the purpose of marriage, one of which was to have children. All informants also share the same view, namely, that child-freedom will be allowed if it contains an emergency (maslahah dharuriyat) for example a couple with a medical history does not allow them to have children. Keywords: Childfree, Descendants, Choice, Character View